TKV-0 was identifled as the causal agent of a disease of Aranda Wendy Scott in Jakarta. Bioasssay showed that the virus prduced 10-1 lesirms m Cassia occidentalis, Chenopodium amzranticolor, Gornphrena ~l obosa , and Nicotiana glutinoaa . Observation of the "dig methoda preparation of diseaaed plant sap under the electron microscope indicated that the virus particles were rod-shaped and right with a length of about 300 mm. - Rusmilah Hari Suseno (Buletin Hama dan Penyakit Tumbuhan, 1979)
TKV-0 was identifled as the causal agent of a disease of Aranda Wendy Scott in Jakarta. Bioasssay showed that the virus prduced 10-1 lesirms m Cassia occidentalis, Chenopodium amzranticolor, Gornphrena ~l obosa , and Nicotiana glutinoaa . Observation of the "dig methoda preparation of diseaaed plant sap under the electron microscope indicated that the virus particles were rod-shaped and right with a length of about 300 mm.